Pengaruh Kualitas Produk Dan Biaya Administrasi Tabungan Easy Wadiah Terhadap Kepuasan Nasabah Bank Syariah Indonesia - Niken Ayu Wulandari; Yunaita Rahmawati (WADIAH, 2023)
A quality product will create its own essence for customers. That way if a company provides a product that exceeds the customer's wishes, the customer will be satisfied. In addition, customers will feel happy and comfortable if they are charged a light administration fee. So, customer satisfaction will increase if administration costs are low. This study aims to test and analyze the partial and simultaneous effect of product quality and administrative costs of easy wadiah savings on the satisfaction of SDIT Qurrota A'yun Ponorogo employees as customers of Bank Syariah Indonesia. The method used in this study is quantitative with probability sampling technique, namely the simple random sampling method and data collection through interviews and questionnaires. The variable testing tool uses SPSS version 22 software. The results obtained through SPSS version 22 show that partially the product quality of easy wadiah savings has an effect on employee satisfaction at SDIT Qurrota A'yun Ponorogo as a customer of Bank Syariah Indonesia and administrative costs of easy wadiah savings have no effect on SDIT Qurrota A'yun Ponorogo employee satisfaction as a customer of Bank Syariah Indonesia; while simultaneously product quality and administrative costs of easy wadiah savings affect the satisfaction of SDIT Qurrota A'yun Ponorogo employees as customers of Bank Syariah Indonesia.